Location Planning Approach for Intermodal Terminals in Urban and Suburban Rail Transport - Petrović, Marjana; Mlinarić, Tomislav Josip; Šemanjski, Ivana (Promet - Traffic&Transportation, 2019)
The aim of this study is to find a suitable methodology for planning the locations of intermodal terminals in an urban transit context. The location planning approach, which has been developed and makes this possible, consists of three phases. The first phase is the making of the geographic information system (GIS) database which enables determining the potential locations of intermodal terminals. For every potential location of the terminal, the number of citizens gravitating to a certain terminal is calculated, which at the same time represents the output from the first phase of the model. The second phase uses an optimization algorithm in order to determine the locations of the intermodal terminals. The optimization algorithm provides several solutions for a different number of terminals, and such solutions need to be evaluated. The main contribution of this research is in upgrading the location planning approach by introducing an additional step in assessing the solutions obtained by the optimization algorithm.